Executive Function Response to Moderate-to-High-Intensity Rope Skipping in Overweight Adolescents Aged 12–14: A Preliminary Study - Qian Yu; Xiaodong Wang; Lin Zhang (Journal of Functional Morphology and Kinesiology)
Background: Previous studies have shown that a high body mass index (BMI) is detrimental to executive function (EF) in children and elderly populations but may be improved by physical activity (PA). However, research on adolescents aged 12–14 is lacking. This study explores two parts: Part 1: cross-sectional correlation between BMI and EF; Part 2: the effect of an 8-week rope skipping intervention. Methods: Recruit 166 adolescents to participate in EF tasks. Screen and select 96 adolescents to be assigned to the normal weight control group (N-C, n = 23) and the normal weight exercise group (N-E, n = 23), the overweight control group (OV-C, n = 13), and the overweight exercise group (OV-E, n = 14), the obese control group (OB-C, n = 12), and the obese exercise group (OB-E, n = 11). Exercise program: moderate-to-high-intensity rope skipping training. Control program: Self-directed reading. Data were recorded for BMI and EF tasks. Results: Part 1, EF and BMI exhibit a negative linear correlation. Part 2, the reaction time of EF tasks in N-E, OV-E and OB-E decreased about 9, 14, 13% (p < 0.05), respectively, while the average BMI in OV-E and OB-E decreased about 10% and 11% (p < 0.05), suggesting a potential correlation between the reduction in BMI and the improvement in EF, which means that the exercise intervention significantly improved EF performance. Conclusions: Among adolescents aged 12–14, overweight and obese individuals exhibit weaker EF compared with normal weight individuals. An 8-week moderate-to-high-intensity rope skipping exercise program can improve EF in adolescents aged 12–14 with different BMIs, and the improvement is greater in overweight and obese individuals.